PRAKTIKUM SEBAGAI MEDIA KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR - Oding Sunardi; Yudhie Suchyadi (Universitas Pakuan, 2020)
PRACTICUM AS A MEDIA FOR PEDAGOGIC COMPETENCY PRIMARY SCHOOL TEACHERSTeacher problems will be increasingly complex, where teachers must have competence in dealing with technological developments. Responding to technological challenges has become the basis of human life. Prepare students who are qualified and able to compete globally, and master technology. The research objective was to improve the pedagogical competence of elementary school teachers through practicum training. The activities in this study consisted of diagnosis, action planning, action taking and action evaluation. Data collection techniques using observation techniques. The observation instrument used was a teacher's ability assessment tool in the form of: 1) learning media development instrument, 2) teacher ability assessment instrument in compiling lesson plans. The data analysis used was a comparative descriptive analysis technique. The quantitative data obtained are described in the form of words or explanations. Then the data comparison was carried out to ensure that there was an increase in the ability of teachers to increase the ability of teachers to develop learning media and prepare lesson plans. The results showed that the practicum can improve a) the ability of elementary school teachers to develop learning media by 27.8%. b) Increasing the ability of elementary school teachers in preparing lesson plans by 39.7%, the findings were successful. From the t-test results, it was found that there were significant differences. This means that understanding of concepts and Science Process Skills (SPS) increases after the teacher experiences the practical learning process of science learning material in practicum. From the results, the average value of conceptual understanding increased from 62.42 to 86.68 and the average value of science process skills increased from 56.19 to 87.86. 94% of teachers responded positively, namely agreeing and strongly agreeing that the science learning process with practicum can improve science process skills and understanding of subject matter for elementary teachers.